THE PROBLEM OF THE FORMATION OF LITERARY COMPETENCE OF SENIOR PUPILS IN THE PROCESS OF ANALYSIS OF ARTISTIC WORKS WITH THE USE OF INNOVATIVE MEANS OF EDUCATION - Palamar, Svitlana; Nazarenko, Lyudmyla (Educological discourse, 2019)
The article deals with the actual problems of emotional and intellectual development and education of youth in the process of studying literature; the motivational readiness of 10-11-grade students for the use of information and communication technologies (ICT) in the subject activity was determined; possible types of reading activity with the use of ICT during the event, analogous, problem-thematic analysis of the artistic work; experimental work evaluations are given. The emphasis is on the text-centric study of literature, the need for the emotional and intellectual perception of the art of the word, readiness for reader activity. The basic ideas of research are described. The reasons for teachers' unpreparedness to use ICT tools in the lessons of Ukrainian literature are singled out. The results of the questionnaire, conducted to determine the level of formation of literary competence (LC) of senior pupils, are summarized. In order to check the levels of literacy and skills development based on research and experimental learning. Developed tasks that take into account the level of the formation of readers' skills, individual peculiarities, the possibility of perceiving a representative school system, developed cross-cutting skills that a senior pupil-reader must possess for the purpose of continuous productive learning. The connection with important practical tasks, indicators of levels of LC formation for high school students by means of ICT is presented. In scientific research, the experience of using ICT during the analysis of artistic work is disclosed. The aesthetic reception and artistic communication (internal and external) between the author, the work and the reader are highlighted.